Changes in DNA methylation persist over time in males with severe alcohol use disorder—A longitudinal follow‐up study. Issue 3 (25th January 2021) - Soundararajan, Soundarya; Agrawal, Arpana; Purushottam, Meera; Anand, Shravanthi Daphne; Shankarappa, Bhagyalakshmi; Sharma, Priyamvada; Jain, Sanjeev; Murthy, Pratima
Abstract: Treatment strategies for alcohol use disorder (AUD) aim for abstinence or harm reduction. While deranged biochemical parameters reverse with alcohol abstinence, whether molecular changes at the epigenetic level reverse is not clearly understood. We investigated whether the reduction from high alcohol use reflects DNA methylation at the gene‐specific and global level. In subjects seeking treatment for severe AUD, we assessed gene‐specific (aldehyde dehydrogenase [ ALDH2 ]/methylene tetrahydrofolate reductase [ MTHFR ]) and global (long interspersed elements [ LINE‐1 ]) methylation across three‐time points (baseline, after detoxification and at an early remission period of 3 months), in peripheral blood leukocytes. We observed that both gene‐specific and global DNA methylation did not change over time, irrespective of the drinking status at 3 months (52% abstained from alcohol). Further, we also compared DNA methylation in AUD subjects with healthy controls. At baseline, there was a significantly higher gene‐specific DNA methylation ( ALDH2 : p < .001 and MTHFR : p = .001) and a significant lower global methylation ( LINE‐1 : p = .014) in AUD as compared to controls. Our results suggest that epigenetic changes at the DNA methylation level associated with severe AUD persist for at least 3 months of treatment.